Resilience of Male Teachers and Prospective Male Teachers as Minorities in the Early Childhood Education Field - Pasiningsih, Pasiningsih; Pancaningrum, Novita (Universitas Islam Negeri Raden Intan Lampung, 2023)
As a minority in the Early Childhood Education (ECE) field, male teachers and prospective male teachers are likely to face some challenges. Therefore, developing resilience skills is needed. This study aims to investigate the resilience factors of male teachers and prospective male teachers as minorities in the ECE field. Identifying the resilience factors of male teachers and male teacher candidates may guide kindergarten leaders and ECE head study programs in higher education to support male participation in the ECE field. It is descriptive qualitative research involving four male teachers and two prospective male teachers in the Kudus area. In-depth interviews were used to collect the data, while a three-phase analysis of Miles and Huberman was used to analyze the data. Findings showed some risk factors that can be challenges in developing resilience, such as the public’s stereotype about men who choose ECE, low salary, and lack of acceptance from others. On the other hand, some protective factors that support their resilience are their love toward children, family, colleagues, and classmates’ support, as well as religious factors. Collaborative efforts are needed to make the ECE field more gender inclusive, including strengthening the protective factors and teaching resilience to prospective male teachers so they can face some challenges that might arise in the fieldwork.